2022
DOI: 10.3390/microorganisms10101981
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Degree of Forest Management on Methylmercury and the Composition of Microbial Communities in the Sediments of Boreal Drainage Ditches

Abstract: Inorganic mercury (Hg) can be methylated to the highly toxic and bioavailable methylmercury (MeHg) by microorganisms in anaerobic environments. The Hg methylation rate may be affected by forest management activities, which can influence the catchment soils, water, and sediments. Here, we investigate the influence of forest management in the form of ditch cleaning and beaver dam removal, as well as the seasonal variations, on sediment chemistry and microbiota. The relationships between MeHg concentrations in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…SRB are usually considered to be strictly anaerobic [ 10 , 62 ]. When studying the tolerance of SRB to oxygen, it was found that some SRB could survive in the aerobic environment, and it was considered that these SRB were facultative anaerobic bacteria [ 11 , 12 , 13 ]. However, Li [ 30 ] screened some aerobic heterotrophic bacteria that can reduce sulfate under anaerobic conditions to produce hydrogen sulfide, including Pseudodesulfovibrio , Vibrio , Photobacterium , and Staphylococcus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRB are usually considered to be strictly anaerobic [ 10 , 62 ]. When studying the tolerance of SRB to oxygen, it was found that some SRB could survive in the aerobic environment, and it was considered that these SRB were facultative anaerobic bacteria [ 11 , 12 , 13 ]. However, Li [ 30 ] screened some aerobic heterotrophic bacteria that can reduce sulfate under anaerobic conditions to produce hydrogen sulfide, including Pseudodesulfovibrio , Vibrio , Photobacterium , and Staphylococcus .…”
Section: Discussionmentioning
confidence: 99%
“…More than 60 genera and more than 220 species of SRB have been reported thus far [ 9 ], including Desulfovibrio , Desulfomonas , Desulfobulbus , and Desulfotomaculum . Traditionally, SRB are considered strictly anaerobic bacteria [ 10 ], but several studies have confirmed that some bacteria can survive in aerobic environments and show oxygen tolerance [ 11 , 12 , 13 ]. These bacteria mainly belong to the genus Desulfovibrio , such as Desulfovibrio vulgaris [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%